2016
DOI: 10.1542/peds.2015-3927
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length in Newborns: Implications for the Role of Telomeres in Human Disease

Abstract: BACKGROUND AND OBJECTIVE: In adults, leukocyte telomere length (LTL) is variable, familial, and longer in women and in offspring conceived by older fathers. Although short LTL is associated with atherosclerotic cardiovascular disease, long LTL is associated with major cancers. The prevailing notion is that LTL is a "telomeric clock, " whose movement (expressed in LTL attrition) reflects the pace of aging. Accordingly, individuals with short LTL are considered to be biologically older than their peers. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
205
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 47 publications
18
205
1
Order By: Relevance
“…Moreover, genetic analyses have revealed that alleles associated with short LTL are also associated with CVD [1012], largely excluding the possibility of reverse causality, i.e., CVD causing LTL shortening. Coupled with observations that LTL, which reflects telomere length in somatic tissues [13], is highly heritable [14,15] and is largely determined at birth [16], these findings suggest that telomere length might play an active role in CVD and longevity. Such a conclusion is relevant to the debate about the existence of a natural lifespan limit for humans [1721].…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, genetic analyses have revealed that alleles associated with short LTL are also associated with CVD [1012], largely excluding the possibility of reverse causality, i.e., CVD causing LTL shortening. Coupled with observations that LTL, which reflects telomere length in somatic tissues [13], is highly heritable [14,15] and is largely determined at birth [16], these findings suggest that telomere length might play an active role in CVD and longevity. Such a conclusion is relevant to the debate about the existence of a natural lifespan limit for humans [1721].…”
Section: Introductionmentioning
confidence: 65%
“…TL, which is a highly heritable complex genetic trait [25–27], displays wide variation across the population, a phenomenon that is already observed at birth [28]. While individuals with constitutively long telomeres are prone to major cancers [7–14], those with constitutively short telomeres are prone to atherosclerotic cardiovascular disease [2931], perhaps the most common human degenerative disease.…”
Section: Evolutionary and Epidemiological Perspectivesmentioning
confidence: 99%
“…Aging starts even before birth, that is why is necessary not only to study telomere length at birth, as a prerequisite to understand its dynamics throughout life, but also to investigate several exposures, and genetic and epigenetic factors that may contribute to accelerate this process [37]. Aging is defined as the time-dependent event that results in a progressive functional decline that affects most living organisms.…”
Section: Telomere Length and Human Healthmentioning
confidence: 99%